Mergulhando em memórias, tecendo culturas e construindo histórias:: o diálogo entre a história e o turismo de base comunitária - Santos da Silva, Francisca de Paula; de Almeida Martins, Luciana Conceição (Sustainability in Debate, 2013)
The objective of this paper is to discuss the dialogical relationship between historical research and community-based tourism (TBC). This is done through the analysis of the sustainability aspects of the social, cultural, and historical memory in contexts which reveal dialectical processes of knowledge construction. In this regard, it is noteworthy that studies on historical research focused on the implementation of community-based tourism are innovative, interdisciplinary and therefore incipient. As such, they reveal elements that represent a theoretical-methodological basis for the used referencials, including a contextualized analysis of an outreach project of the University of Bahia (UNEB) on community-based tourism, developed at the city of Cabula and its surroundings in Salvador, Bahia state. Conclusions reveal potentialities in historical research, as evidenced by the close association of the studied actors, practices and topics.